How fragmentation affects insect predation rate : a Singapore case study - See, Angelica Rui Xiao (2018)
Over the last 150 years, the tropical forests in Singapore have been rapidly fragmented and urbanised but the effects of fragmentation remain poorly understood. In this study, I sought to understand how fragmentation may impact forest functioning and health through studying insect predation rate by using artificial caterpillars. I measured how fragment edge effects and forest patch size affected insect predation rate by using three separate forest fragments which differed in size and shape. Insect predation rate was found to increase with increasing distance away from the forest edge, although the relationship between edge effects and insect predation rate was very weak. Forest patch size was found to have no effect. This study highlights the importance in studying fragmentation effects on insect activity and response, especially in a highly urbanised setting such as Singapore where most forests have been heavily degraded and reduced to isolated patches.